PREVALENCE OF CHLAMYDIA TRACHOMATIS AMONG ASYMPTOMATIC WOMEN - Qayum, Mamuna; -bin-Saleem, Muhammad Khalid (Journal of Ayub Medical College Abbottabad, 2013)
Background: Chlamydia trachomatis is a ubiquitous pathogen worldwide and causes ocular, urogenital, and respiratory infections in humans. C. trachomatis infection of lower genital tract is one of the most prevalent sexually transmitted diseases (STDs) in different parts of the world. Their treatment, follow-up, and hopefulness for future is very important. Objectives of this study were to see the prevalence of Chlamydia trachomatis infection among women of child bearing age and to determine the incidence of Chlamydia infection in neonates of women infected with Chlamydia. Methods: This observational study was carried out in Department of Obstetrics & Gynaecology, CMH Abbottabad, and Department of Ophthalmology, Women Medical College Abbottabad from January 2012 to June 2012. Urine samples were collected from 200 women aged 20-39 years attending Obs/Gyn Department of CMH Abbottabad. After delivery, babies who were born to mothers with infection of their genital tracts were examined with a 2.5Ã—binocular loupe within a week of birth to rule out eye infection (Chlamydia Ophthalmic neonatorum). Results: The overall prevalence of Chlamydia trachomatis was 4% in 200 eligible patients. The overall incidence of Chlamydia trachomatis in neonates was 1.66%. Conclusion: A significant proportion of women resident of Abbottabad District expressed evidence of exposure to Chlamydia trachomatis and significant number of neonate eyes were infected with the pathogen. Keywords: Chlamydia trachomatis, Chlamydia ophthalmic neonatorum, Sexually Transmitted Disease